Fourier transform ion cyclotron resonance mass spectrometry at the true cyclotron frequency. Issue 2 (18th January 2021) - Nagornov, Konstantin O.; Tsybin, Oleg Y.; Nicol, Edith; Kozhinov, Anton N.; Tsybin, Yury O.
Abstract: Ion cyclotron resonance (ICR) cells provide stability and coherence of ion oscillations in crossed electric and magnetic fields over extended periods of time. Using the Fourier transform enables precise measurements of ion oscillation frequencies. These precisely measured frequencies are converted into highly accurate mass‐to‐charge ratios of the analyte ions by calibration procedures. In terms of resolution and mass accuracy, Fourier transform ICR mass spectrometry (FT‐ICR MS) offers the highest performance of any MS technology. This is reflected in its wide range of applications. However, in the most challenging MS application, for example, imaging, enhancements in the mass accuracy of fluctuating ion fluxes are required to continue advancing the field. One approach is to shift the ion signal power into the peak corresponding to the true cyclotron frequency instead of the reduced cyclotron frequency peak. The benefits of measuring the true cyclotron frequency include increased tolerance to electric fields within the ICR cell, which enhances frequency measurement precision. As a result, many attempts to implement this mode of FT‐ICR MS operation have occurred. Examples of true cyclotron frequency measurements include detection of magnetron inter‐harmonics of the reduced cyclotron frequency (i.e., the sidebands), trapping field‐free (i.e., screened) ICR cells, and hyperbolic ICR cells with quadrupolar ion detection. More recently, ICR cells with spatially distributed ion clouds have demonstrated attractive performance characteristics for true cyclotron frequency ion detection. Here, we review the corresponding developments in FT‐ICR MS over the past 40 years.